KORELASI DUKUNGAN SUAMI DAN JUMLAH ANAK TERHADAP PENGGUNAAN ALAT KONTRASEPSI OLEH WUS - Putra, Bayu Pratama; Purnomo, Sandy Kartika (Ensiklopedia of Journal, 2024)
Contraceptive use is one of the indicators of the 2020-2024 National Medium-Term Development Plan (RPJMN) to create a prosperous society. The NTT Province health profile report in 2023 showed that the number of inactive family planning participants was 40.3%. Wemeda Village is one of the villages that has the lowest number of family planning users compared to other villages. The purpose of the study was to determine the correlation of husband support and the number of children to the use of contraceptives by WUS. The type of research is quantitative with a cross sectional design. This research was conducted in Waemeda Village, East Malacca Sub-district, Malacca Regency in November 2022. The population is all women of childbearing age in Waemeda Village, which is 310 people. The sample amounted to 73 people selected using simple random sampling technique. The research instrument used a research questionnaire. Data analysis was done univariate and bivariate. The results showed that there was a relationship between husband support (p value: 0.015) and the number of children (p value: 0.021) with the use of contraceptives in women of childbearing age. It is recommended for health workers to be more active in providing health information to improve IEC on the use of contraceptives in women of childbearing age, besides that it is expected that health workers, especially the person in charge of the family planning program and family planning field officers in Wemeda Village, should further increase socialization to the community, especially to women of childbearing age.